Misrepresentation of Religious Tenet in Syed Waliullah’s Tree Without Roots [Lal Shalu]: An Islamic Overview - Uddin, Mohammad Jashim (Muslim English Literature, 2022)
AbstractSyed Waliullah is one of the most versatile Muslim novelists in Bangladesh. Social reformation, awakening people about religion and satire against corruption are his main themes. He also identifies the peripheral community in his writings. His Tree Without Roots originally Lal Shalu in Bangla is the most popular novel for its multilevel portrayal of the Bengali Muslim community. The paper aims at focusing on how Islam and its followers are portrayed wrongly in Tree Without Roots because the novelist through the activities of Majeed wants to divert the mass Muslims from the Qur’anic guidelines to the man-made path for worldly benefits. It concentrates on the controversial protagonist Abdul Majeed who grasps the rural people especially the simple and innocent like women for his greater projection of power and hunger. As a part of his prosperity, Majeed deeply feels inside himself that women can be the most flexible and reliable field for smooth cultivation and experimental adventure. This paper has also traced the sources of the power of Majeed—the protagonist, that he uses to manipulate the villagers and to claim his influential position in Mahabbatpur – a fictional village of Bangladesh which was then East Pakistan. It has focused on the activities of the characters from an Islamic perspective. The paper believes that every Muslim should follow the instructions of Allah reviled in the Qur’an and the path shown in the Hadith by Prophet Muhammad (pbuh). Finally, the paper has found some ways the author has misrepresented Islam in his writing from a modernist perspective.